2016
DOI: 10.1093/eurheartj/suw008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous l-carnitine in Chinese patients with chronic heart failure

Abstract: Chronic heart failure (CHF) may be associated with an energy deficit in cardiac muscle. As levo-carnitine (LC) is involved in the production of myocardial energy, it is hypothesized that LC supplementation may ameliorate CHF symptoms. This multicentre, randomized, double-blind, and placebo-controlled study included 265 patients with CHF. Patients were randomized to receive either LC or placebo, twice a day. Endpoints were measured after 7 days of treatment. Primary endpoint was a reduction of at least one NYHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Four studies [ 12 , 13 , 21 , 26 ] did not report the method of randomization, whereas the others reported a randomization number sequence or adaptive minimization randomization scheme. There were three studies [ 13 , 17 , 26 ] using the blind method; blind methods of all the other studies are unclear. One study [ 21 ] had high performance bias for the reason that more than 20% of patients were lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [ 12 , 13 , 21 , 26 ] did not report the method of randomization, whereas the others reported a randomization number sequence or adaptive minimization randomization scheme. There were three studies [ 13 , 17 , 26 ] using the blind method; blind methods of all the other studies are unclear. One study [ 21 ] had high performance bias for the reason that more than 20% of patients were lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 21 ] had high performance bias for the reason that more than 20% of patients were lost to follow-up. Selective reporting was found in three studies [ 13 , 21 , 26 ] because they did not present the ITT analysis data. These studies had high performance bias and detection bias.…”
Section: Resultsmentioning
confidence: 99%
“…The 6minute walk test did not show significant difference between control and intervention (P = 0.14). 9 The study from Song X et al also showed that carnitine had positive effect on serum-BNP (P = 0.01) and NT-proBNP (P = 0.0003). Both BNP and NT-proBNP can act as prognostic factors in patients with heart failure or in patients with asymptomatic left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…8 Even so, giving carnitine can be a nutritional therapy for patients with heart failure that can help improve heart function and the quality of life of patients. Jing et al 9 carried out a research by administering carnitine intravenously twice a day for seven days, in the form of 1 g of L-carnitine dissolved in 100mL of normal saline in patients with heart failure. The assessment was carried out on the NYHA class of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, several studies suggest that carnitine could improve mental health in older adults with mild cognitive impairment or Alzheimer’s disease [ 15 ]. Carnitine may also improve other age-associated diseases such as cardiovascular diseases [ 16 19 ], atherosclerosis [ 20 ], neurometabolic disorders [ 21 ] and diabetic symptoms [ 22 25 ]. In addition, carnitine has also been used in adjuvant therapy to treat conditions such ashemodialysis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%